Household air pollution, ultrasound measurement, fetal biometric parameters and intrauterine growth restriction - Anindita Dutta; Donee Alexander; Theodore Karrison; Oludare Morhasson-Bello; Nathaniel Wilson; Omolola Mojisola Atalabi; Damilola Adu; Tope Ibigbami; Samuel Adekunle; Dayo Adepoju; John Olamijulo; Omolola Akinwunmi; et al. (BMC, 2021)
Abstract Background Low birthweight, intrauterine growth restriction (IUGR) and perinatal mortality have been associated with air pollution. However, intervention studies that use ultrasound measurements to assess the effects of household air pollution (HAP) on fetal biometric parameters (FBP) are rare. We investigated the effect of a cookstove intervention on FBP and IUGR in a randomized controlled trial (RCT) cohort of HAP-exposed pregnant Nigerian women. Methods We recruited 324 women early in the second trimester of pregnancy. Between 16 and 18 weeks, we randomized them to either continue cooking with firewood/kerosene (control group) or receive a CleanCook stove and ethanol fuel (intervention group). We measured fetal biparietal diameter (BPD), head circumference (HC), femur length (FL), abdominal circumference (AC) and ultrasound-estimated fetal weight (U-EFW) in the second and third trimesters. The women were clinically followed up at six regular time points during their pregnancies. Once during the women's second trimester and once during the third, we made 72-h continuous measurements of their personal exposures to particulate matter having aerodynamic diameter < 2.5 μm (PM2.5). We adopted a modified intent-to-treat approach for the analysis. Differences between the intervention and control groups on impact of HAP on fetal growth trajectories were analyzed using mixed effects regression models. Results There were no significant differences in fetal growth trajectories between the intervention and control groups. Conclusions Larger studies in a setting of low ambient air pollution are required to further investigate the effect of transitioning to a cleaner fuel such as ethanol on intrauterine growth. Trial registration ClinicalTrials.gov NCT02394574 ; September 2012